Atividade antimicrobiana da cobertura comestível de quitosana adicionada com trans-cinamaldeído sobre Escherichia coli E Listeria innocua em melão cantaloupe (Cucumus melo, L.) minimamente processado. - Ugarte, Sheila Dayanna Milan (2012)
The consumption of fresh-cut fruits have grown considerably in recent years due to its nutritional advantages and because these are ready-to-eat products. However, the potential presence of pathogenic microorganisms in these products is a health risk for consumers, as they are eaten raw. The main purpose of this research was to evaluate in vivo the efficiency of a chitosan edible coating added with trans-cinnamaldehyde applied to fresh-cut melon (Cucumis melo L.), against fresh-cut melon’s own microflora and against Escherichia coli (ATCC 25922TM) and Listeria innocua (ATCC 33090). Firstly, in order to obtain the effective antimicrobial concentration, the Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) were obtained in vitro. Subsequently, the melons were minimally processed and divided into three parts, the first part without inoculation, the second part inoculated with E. coli and the third part inoculated with L. inocua; immediately, the fresh-cut melon was immersed in two types of edible coating: a medium molecular weight chitosan edible coating (2%) and a chitosan edible coating added with trans-cinnamaldehyde (0.05%). Fresh-cut melon inoculated with water, inoculated with E. coli and inoculated with L. inocua, was used as controls. The determination of mesophilic bacteria, psychrophilic, coliform, yeasts and moulds was realized in non inoculated fresh-cut melon. In the other hand, the counting of E. coli and L. innocua was realized in inoculated fresh-cut melon; these microbiological analysis were done, in times: 0, 3, 7, 14 and 21 days of storage at 4 °C. Both edible coatings showed antimicrobial action against E. coli and L. innocua, mesophilic, psychrophilic, coliform bacterias, yeasts and moulds, no statistically significant difference was found between them (P>0,001). The chitosan edible coating added with trans-cinnamaldehyde (0.05%) do not show improved efficiency in its antimicrobial action, regarding the microorganisms used in this research.